Economic crisis and blood donation: How are donors' motivations changing?. Issue 3 (June 2016) - Alfieri, Sara; Guiddi, Paolo; Marta, Elena; Saturni, Vincenzo
Abstract: Background: The economic crisis has exasperated people's feelings of loneliness; job instability often does not allow people to commit to voluntary work. The present work proposes to examine whether the motivations to donate blood have changed before and during the period of economic crisis, taking into consideration donors' gender. We adopted Omoto & Snyder's functionalist approach, which states that blood donation serves different functions for any one person, who may have different motivations from those held by other people. Materials and Methods: We compared six-year pre–post (t1 "pre-crisis": 2008 – t2 "during the crisis": 2014) data on a sample of blood donors in a single blood donation center situated in Northern Italy. T-test was used for data analysis. Three hundred thirty donors (age range 18–60, M = 32.6, SD = 9.53; 54.5% male) were administered a survey at t1 and 444 (age range 18–60, M = 37.8, SD = 10.16; 68% male) six years later at t2. In both surveys, participants were administered a questionnaire with socio-demographic items and a version of Omoto & Snyder's Motivations to Volunteer scale adapted to blood donation. Results: Donors' motivation priorities did not vary over time. Values and Self-enhancement motivations are the most prevalent. Knowledge and Ego-protection motivations decreased with the upsurge of the crisis. Women, in general, report higher mean values than men do for Values and Ego-protection motivations. Conclusion: These results can offer valuable clues for the agencies that manage blood collection.